Cutaneous Leishmaniasis: A Neglected Vector Borne Tropical Disease in Midwestern Region of Nepal - Pragya Gautam Ghimire; Richa Shrestha; Sumit Pandey; Kumar Pokhrel; Rajan Pande (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Cutaneous Leishmaniasis is a vector borne disease caused by the bite of an infected sandfly. The disease is rare in Nepal with only few cases reported till date. We report the largest collection of patients over six years.